2006
DOI: 10.1089/cap.2006.16.91
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Benefit and the Risk of Suicidality in Multicenter, Randomized, Controlled Trials of Sertraline in Children and Adolescents

Abstract: With the stipulation that doctor and patient preferences necessarily play a critical role in the choice of treatment, NNT to NNH ratios indicate a positive benefit-to-risk ratio for sertraline in adolescents with MDD and in patients of all ages with OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Trials and reviews of SSRIs are the most commonly studies biological intervention and generally conclude that there is evidence for the effectiveness of fluoxetine compared with placebo, with inconsistent evidence for other medications in this class [5154, 70]. However the clinical significance of the results from these trials have been described as far from compelling, with criticisms directed at methodological aspects of the trials including high drop-out rates and high placebo-response rates, concerns about the measurement tools used with questions raised about whether the difference in effect between SSRIs and placebo reflects a difference that is of clinical importance to patients, and concerns about the representativeness of the included participants [54].…”
Section: Discussionmentioning
confidence: 99%
“…Trials and reviews of SSRIs are the most commonly studies biological intervention and generally conclude that there is evidence for the effectiveness of fluoxetine compared with placebo, with inconsistent evidence for other medications in this class [5154, 70]. However the clinical significance of the results from these trials have been described as far from compelling, with criticisms directed at methodological aspects of the trials including high drop-out rates and high placebo-response rates, concerns about the measurement tools used with questions raised about whether the difference in effect between SSRIs and placebo reflects a difference that is of clinical importance to patients, and concerns about the representativeness of the included participants [54].…”
Section: Discussionmentioning
confidence: 99%
“…13,15,22 Children may be at higher risk of suicidal thoughts and behaviours when treated with antidepressants than adolescents. 17 Those children and adolescents treated with antidepressants for anxiety disorders did not have an increased risk of suicidal thoughts and behaviours in three of the studies. 16,17,20 The most recent Cochrane review (2012) included 19 published and unpublished RCTs (n = 3335 participants) that compared newer generation antidepressants with placebo in children and adolescents (6-18 years) who were diagnosed with a depressive disorder.…”
Section: Meta-analysesmentioning
confidence: 90%
“…17 Those children and adolescents treated with antidepressants for anxiety disorders did not have an increased risk of suicidal thoughts and behaviours in three of the studies. 16,17,20 The most recent Cochrane review (2012) included 19 published and unpublished RCTs (n = 3335 participants) that compared newer generation antidepressants with placebo in children and adolescents (6-18 years) who were diagnosed with a depressive disorder. 22 This Cochrane review used two outcome measures: (i) suicide-related outcomes (thoughts and behaviours) as reported in Hammad 6 and (ii) suicidal thinking as measured by the Suicidal Ideation Questionnaire-Junior High School Version (SIQ-Jr).…”
Section: Meta-analysesmentioning
confidence: 90%
“…March et al 5 reported that the NNH for suicidality was 64 when sertraline was used to treat pediatric depression. This means that 64 depressed children and adolescents need to receive sertraline for 1 extra patient to experience suicidality as an adverse outcome.…”
Section: Understanding Nnhmentioning
confidence: 99%